A neural network classifier for detecting diabetic retinopathy from retinal images - M. M. Lukashevich (Системный анализ и прикладная информатика, 2023)
With the spread of diabetes mellitus, diabetic retinopathy (DR) is becoming a major public health problem (especially in developing countries). The long-term complications resulting from DR have a significant impact on patients. Early diagnosis and subsequent treatment can reduce the damage to health. Predictive analytics can be based on the analysis of human retinal images using convolutional neural networks. In this paper, the research focuses on the development of an efficient method for DR detection based on the EfficientNet convolutional neural network, self-learning technology and data augmentation operations. As a result of the experiments, a neural network classifier based on convolutional neural networks is developed, recommendations for data augmentation operations are given. Experiments were performed on the public dataset and showed that it is possible to achieve the proportion of correctly classified objects equal to 97.14 % on the test set from the public dataset.